Effects of situational efficiency indicators on final outcome among male basketball teams on the Olympic Games in London 2012 - Milanovic, D.; Stefan, L.; Sporis, G.; Vuleta, D.; Selmanovic, A. (Acta Kinesiologica, 2016)
The aim of the present study was to determine which situational efficiency parameters influenced the most on the final result among male basketball teams. Sample of entities was consisted of 38 games played on the Olympic Games in London 2012. Sample of variables was comprised of 13 indicators that determined final result and affecting overall game. For presenting basic values of each variable, descriptive statistics was used. Multiple regression analysis was used to determine which variables influenced the most on final results of the game. Significance was set up at p.0,05. Results showed that 2 points-fail (t-value= -3,85; ƒÀ coefficient= -0,55; p<0,01), 3 points-fail (t-value= -2,36; ƒÀ coefficient= -0,28; p<0,05), offensive rebounds (t-value= 4,05; ƒÀ coefficient= 0,55; p<0,01), defensive rebounds (t-value= 2,58; ƒÀ coefficient= 0,25; p<0,05), turnovers (t-value= -3,75; ƒÀ coefficient= -0,36; p<0,01) and steals (t-value= 2,19; ƒÀ coefficient= 0,21; p<0,05) statistically had impact on the final results of the game. In conclusion, successful teams performed better in shooting elements, along with rebounds and steals, which gave them opportunity to gain the advantage opposed to the opponent and win the competition.